An isolated bacterial consortium for crude oil biodegradation - Al-Khatib, Ma'an Fahmi Rashid; Alam, Md. Zahangir; Muyibi, Suleyman Aremu; Husain, Iman A. F. (Academic Journals, 2011)
Crude oil utilizing bacteria were isolated from crude-oil contaminated soil (COCS) and tested for their ability to degrade COCS. Fifty strains were isolated, purified and monitored on agar plated for their growth. Twenty strains were selected for the second monitoring in shake flask using minimal salt medium with crude oil as sole carbon source. The growth was monitored by measuring the optical density (OD600) on daily basis. The twelve best growing strains were selected to form four bacterial consortiums. Each consortium contains three strains combined in accordance with their growth. The four consortiums were tested for their growth and the best one (Cons.1) was selected for the kinetics study and the biodegradability test. The first order kinetic study showed that the µmax of Cons.1 was 0.02 h -1 while the half saturation constant ks was 2.2 %v/v TPH. The strains forming IMNC201 belong to Klebsiella pneumoniae and Enterobacteriaceae species. The bioremediation experiments were designed using DesignExpert 6.0.8 software by optimizing the amount of crude oil, microbial inoculum and sludge which are initially added to the autoclaved soil. Fifteen runs were carried out until no more microbial activity was noticed. The bioremediation results were compared with natural attenuation and biostimulation to determine the feasibility of the bioremediation process. From the optimization of the bioremediation, the optimum degradation obtained was 98.8% within 4 days at 5% v/w crude oil, 5% v/w inoculum and 10% v/w sludge. Biostimulation showed 98.3% TPH removal, while natural attenuation resulted in 97.7% in 13 days. The removal of crude oil by bioremediation was achieved in less time as compared to natural attenuation and biostimulation.